RANCANG BANGUN SISTEM INFORMASI PENGENDALIAN PERSEDIAAN OBAT PADA APOTEK ABC JAMBI (STUDI KASUS: OBAT ANTIBIOTIK) - Maria Rosario (JURNAL AKADEMIKA)
Apotek ABC Jambi not currently doing the inventory control of the drugs are sold. Determination of the inventory is still done with the personal considerations of the warehouse. This o f course would be detrimental to Apotek ABC Jambi because if supply many result in the emergence of additional costs due to the inventory. However, if a small supply company likely can not meet the needs of consumers. It is necessary for optimal inventory management. This study discusses the analysis and design the control of drug inventory system which will be supported by the information system. The tool used is the object-oriented approach that is UML (Unified Modeling Language which consists of Use Case Diagram, Class Diagram and Activity Diagram. The study produced a prototype which will be developed into an information system that can be used as decisio making on controlling the supply of drugs in Apotek ABC Jambi.